Redox reactivity control through electromerism - Osterbrink, Johanna; Santos, Fabricio dos; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2024)
In this work, we demonstrate that electromerism could be used to regulate the redox reactivity. Electron self-exchange rates kex were measured for a series of diamagnetic, monocationic CuI complexes with two redox-active diguanidine ligands and the corresponding paramagnetic, dicationic complexes. The electronic structures of the paramagnetic, dicationic complexes differ. Some complexes are exclusively present as CuII complexes with reduced, neutral diguanidine ligands. In other complexes, an equilibrium is established between the CuII electromer and the CuI electromer with the unpaired electron delocalized on the two partially-oxidized ligands. For these complexes, the kex values increase with increasing contribution of the CuI electromer. One of the dicationic molecules is exclusively present as CuI complex with radical ligands in dichloromethane at room temperature, and as CuII electromer with neutral ligands at 200 K. Consequently, the electron self-exchange rate kex is maximal at room temperature, and strongly decreases with decreasing temperature. The temperature effect is much stronger than for similar complexes that remain in the CuII form at all temperatures, demonstrating the use of electromerism to control the redox reactivity on a large scale.
Zuerst veröffentlicht: 07. Februar 2024
Gesehen am 11.07.2024